PENERAPAN KEGIATAN LITERASI UNTUK MENGATASI ADIKSI SMARTPHONE PADA PROSES PEMBELAJARAN DI TINGKAT SMA - Sri Mulyati; Nur Andini; Restu Bias Primandhika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The smartphone is an electronic device that is portable or easy to carry everywhere. The influence of technology makes students dependent on smartphones, causing various impact. The Negative effects that occur in the brain result are difficulty in concentrating the real world, wasted time, and others. Does will possibility generating the learning process which shows students are not optimal. Response-stimulus of time from learning activities very disturbing when students play which smartphones then listening will explain the material. Therefore, the process of cognitive absorption is lower. The positive impacts of smartphones are to facilitate communications, increase knowledge, the emergence of new learning methods. Literacy is the ability to read and write. Literacy movements can reduce addiction on the smartphone, especially during learning. Besides counseling about smartphone use. The purpose of the study is to find out the result of the students’ captivity during learning to describe phenomena that occur in the classroom during the learning process. The method applied to collect the questionnaire through the description. This research was conducted in SMAN 1 Batujajar, a sample of class XI IPS 3 which contained 41 people. The result of this study indicates that the influence of smartphones can inhibit the learning process.